Pesher and hypomnema : a comparison of two commentary collections from the Hellenistic-Roman period - Hartog, Pieter B. (Studies on the Texts of the Desert of Judah, 2017)
In Pesher and Hypomnema Pieter B. Hartog compares ancient Jewish commentaries on the Hebrew Bible with papyrus commentaries on the Iliad . Hartog shows that members of the movement which produced and preserved the Dead Sea Scrolls adopted classical commentary writing and adapted it to their own needs. The connection between the Qumran Pesharim and Hypomnemata on the Iliad resulted from exchanges of scholarly knowledge across Hellenistic-Roman Egypt and Palestine. Analysing the effects of these knowledge exchanges, Pesher and Hypomnema demonstrates that members of the Qumran movement were thoroughly embedded within their Hellenistic and Roman environment.